2013
DOI: 10.1186/1471-2164-14-202
|View full text |Cite
|
Sign up to set email alerts
|

The genome and transcriptome of perennial ryegrass mitochondria

Abstract: BackgroundPerennial ryegrass (Lolium perenne L.) is one of the most important forage and turf grass species of temperate regions worldwide. Its mitochondrial genome is inherited maternally and contains genes that can influence traits of agricultural importance. Moreover, the DNA sequence of mitochondrial genomes has been established and compared for a large number of species in order to characterize evolutionary relationships. Therefore, it is crucial to understand the organization of the mitochondrial genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…In spite of the fact that all proteins encoded in mitochondrial DNA are subunits in the constitutively expressed respiratory complexes or appear to be essential housekeeping proteins, the finding of "only" 71 PPR proteins indicates that many RNA-related processes are inactive in POM. In mitochondria from perennial ryegrass (Lolium perenne) reproductive tissues, a transcript profile showed that the expression of several mitochondrially expressed ribosomal proteins was very low (Islam et al, 2013). This may mean that their expression, and the associated RNA-related processes including PPR proteins, are dependent on the tissue and/or environmental conditions.…”
Section: Ppr Proteinsmentioning
confidence: 99%
“…In spite of the fact that all proteins encoded in mitochondrial DNA are subunits in the constitutively expressed respiratory complexes or appear to be essential housekeeping proteins, the finding of "only" 71 PPR proteins indicates that many RNA-related processes are inactive in POM. In mitochondria from perennial ryegrass (Lolium perenne) reproductive tissues, a transcript profile showed that the expression of several mitochondrially expressed ribosomal proteins was very low (Islam et al, 2013). This may mean that their expression, and the associated RNA-related processes including PPR proteins, are dependent on the tissue and/or environmental conditions.…”
Section: Ppr Proteinsmentioning
confidence: 99%
“…Comparison of the scaffolded assembly with published mitochondrial and chloroplast sequences for Lolium (Islam et al 2013 ;Diekmann et al 2008 ) identifi ed three scaffolds that were mitochondrial in origin and two that were chloroplast in origin. Removal of mitochondrial and chloroplast scaffolds resulted in a genomic assembly containing 424,745 scaffolds and with N50 of 25,193.…”
Section: Genome Assemblymentioning
confidence: 97%
“…Fujii et al ( 2011 ) have very recently characterized the continuously expressed ORFs present in the intergenic region of mitochondrial genome of rice. Similarly, Islam et al ( 2013 ) have presented the mitochondrial genome and transcriptome sequence analyses of perennial ryegrass ( Lolium perenne L.), but still it lacks the detailed transcript mapping and promoter identifi cation. In contrast to plant mitochondrial transcriptome data, human mitochondrial transcriptome has been analyzed more comprehensively across different cell lines and tissues (Mercer et al 2011 ).…”
Section: Transcriptional Regulation and Transcriptomementioning
confidence: 98%